2012
DOI: 10.1159/000334999
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy for Prostate Cancer Does Not Increase Cardiovascular Mortality in the Long Term

Abstract: Objective: To determine if 6 months of neo-adjuvant androgen deprivation is associated with the long-term risk of cardiac mortality. Methods: In the TROG 96.01 trial, 802 men with locally advanced prostate cancer were randomized to radiotherapy either alone or with 3 or 6 months of neo-adjuvant androgen deprivation therapy (NADT). Competing risk methodology was used to derive the cumulative incidence of fatal cardiac events. Results: At 10 years, the cumulative incidence of fatal cardiac events for the radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…They concluded that longer duration of adjuvant GnRHa therapy did not appear to increase CV mortality. Other studies and a recent meta-analysis have reported similar findings [4,16,19,25].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…They concluded that longer duration of adjuvant GnRHa therapy did not appear to increase CV mortality. Other studies and a recent meta-analysis have reported similar findings [4,16,19,25].…”
Section: Discussionsupporting
confidence: 67%
“…The benefit of ADT in patients with an optimal indication prevails over the potential risk of CV mortality [11,16,19,22,26]. 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Daskavich et al (7) published long-term follow-up of the Prostate Cancer Outcomes Study showing that older men (aged ≥ 60 years) with multiple comorbidities are far more likely to die from other causes than prostate cancer. On the other hand, some studies have found no association between ADT and increased cardiovascular risk or morbidity (8)(9)(10)(11)(12)(13)(14). Thus, the relationship between ADT and cardiovascular diseases remains still controversial.…”
Section: Introductionmentioning
confidence: 99%